1993
DOI: 10.1071/ch9931897
|View full text |Cite
|
Sign up to set email alerts
|

Bismuth Ruthenium Oxides. Neutron Diffraction and Photoelectron Spectroscopic Study of Bi2Ru2O7 and Bi3Ru3O11

Abstract: The structures of Bi3Ru3O11, a = 9.3050(2)Ǻ, Pn3, and Bi2Ru2O7, a = 10.2957(1)Ǻ, Fd3m, have been redetermined by Rietveld analysis of powder neutron diffraction data. For both compounds there is no evidence for appreciable oxygen non- stoichiometry . X-Ray photoelectron spectra of both compounds show unusual line shapes. In the case of Bi3Ru3O11 this is a result of the mixed valency and surface oxidation. In Bi2Ru2O7 final state effects appear to be important.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
46
2

Year Published

1996
1996
2000
2000

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 51 publications
(50 citation statements)
references
References 0 publications
2
46
2
Order By: Relevance
“…At the same time the decrease in r 3ϩ A for the 8 ruthenate pyrochlores A 2 Ru 2 O 7Ϫy , A ϭ Pr, x lessens the apparent compression in the AO 8 scaleheNd, Y, Tb, Yb, Bi, Tl(LT), and Tl(HT), the structures of dron, the two A-O(2) bonds along the Ϫ3 axis are noticewhich have been determined using powder neutron diffrac-ably shorter than the other six, equidistant, A-O(1) distion (3,15,25). It is immediately apparent from this figure tances (Table 2).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…At the same time the decrease in r 3ϩ A for the 8 ruthenate pyrochlores A 2 Ru 2 O 7Ϫy , A ϭ Pr, x lessens the apparent compression in the AO 8 scaleheNd, Y, Tb, Yb, Bi, Tl(LT), and Tl(HT), the structures of dron, the two A-O(2) bonds along the Ϫ3 axis are noticewhich have been determined using powder neutron diffrac-ably shorter than the other six, equidistant, A-O(1) distion (3,15,25). It is immediately apparent from this figure tances (Table 2).…”
Section: Resultsmentioning
confidence: 99%
“…Bi 2 Ru 2 O 7 was reported by Facer et al (3) in which the Ru-O distance was found to be 1.983 Å and the RuAll structural refinements were performed using a version of Hill and Howard's program LHPM (20), modified O-Ru angle 133.14Њ. Using the criteria of Kanno et al, these data suggest that this metallic oxide should in fact for a personal computer.…”
Section: Introductionmentioning
confidence: 92%
See 2 more Smart Citations
“…It is not uncommon for transition metal pyrochlores to exhibit a metal}nonmetal transition. A further example of the variable physical properties of the pyrochlores comes from studies of Bi Ru O \ by Carbonio and co-workers (17) who extended our previous work (18) and showed that it is possible to control the oxygen stoichiometry, and hence the structure and conductivity of Bi Ru O \ , by altering the annealing conditions. In parallel with these studies on unsubstituted pyrochlores, Kanno (22).…”
Section: Introductionmentioning
confidence: 97%